Numerical modeling of coaxial wire-powder laser directed energy deposition process in dissimilar metal additive manufacturing - Stephanie B. Lawson; Dongqing Yan; Ali Tabei; Brian K. Paul; Somayeh Pasebani (Results in Materials)
Coaxial wire-fed powder-fed directed energy deposition (CWP-DED), a single-step additive manufacturing process, offers the unique capability of producing tailored dissimilar metals by combining the high deposition rates of wire-based DED with the high resolution and complexity of powder-based DED. Modeling this process for its thermal profile and solidification morphology is crucial for understanding key outcomes such as dimensional accuracy and material composition. In this study, a CWP-DED system is simulated through the development of a computational fluid dynamics (CFD) numerical model. This model captures in-situ thermal profiling and heat transfer interactions within the process while simultaneously providing bead dimensions and weight percentages of the individual materials for wire and powder feedstocks. Simulation results demonstrated strong agreement with experimental data, indicating a robust understanding of the CWP-DED process for dissimilar metal additive manufacturing. These findings contribute to advancements in the synthesis, processing, joining and tailoring of dissimilar metal systems, offering new insights into the design of multi-materials systems.